Mathilde Hollitscher, fashion designer: On the question of obscure pages of Sigmund Freud’s biography and 20th century women’s creative labour - O. M. Lebedeva (Шаги, 2023)
The article is devoted to an analysis of some aspects, professional as well as creative ones, of the biography of Mathilde Hollitscher, Sigmund Freud’s eldest daughter. In this context her life story is presented as a point of convergence of several research trajectories, including the history of the psychoanalytic movement and biographical studies related to the founder of psychoanalysis and his relationship with the world of clothing and textiles. At the same time, this research focuses on the shift of the practices of women’s creative work from the invisible area of domestic labour to the sphere of professional activity implemented in the public space in the 20th century. The article considers the professional life of Freud’s eldest daughter as an illustrative example of such deterritorialization, and also outlines the connections of the Freud family with the world of textiles and clothing. All this opens up new possibilities to elucidate a number of episodes in the history of the psychoanalytic movement, as well as some facts of Sigmund Freud’s biography. The presented materials also create additional perspectives for comprehending the legacy of the founder of psychoanalysis.